From policy to practice : UNFPA's role in the changing aid and development environment (United Nations Population Fund [UNFPA] New YorkUS, 2009)
Addresses the principles of UNFPA's response to the changing aid and development enviroment; countries' expectation that the UN will deliver on global commitments; capacity development and technical assistance, locating capacity development in the policy environment.
Keywords: DEVELOPMENT AID